Konsep Mantra Pengobatan Masyarakat Suku Kokoda dan Manfaatnya Bagi Pendidikan Bahasa - Abdul Hafid; Teguh Yuliandri Putra (Jurnal KIBASP (Kajian Bahasa, Sastra dan Pengajaran), 2019)
The research aims at explaining the structure and the function of treatment spell in Kokoda community as well as explaining the pragmatic function of treatment spell in language education. The research was a qualitative research. It was conducted in Kokoda community, Sorong regency. The informants consist of two main informants and two supporting informants. The techniques in collecting the data were observation, interview and doccumentation. The data were analyzed through interactive model by Miles and Huberman. The findings were 1) the treatment spell was various and unstructured 2) the function of the treatment spell was magical, means can cure any diseases 3) pragmatic finding showed that the spell can bebas teaching resource in Indonesian language. In conclusion, the structure of the spell consist of four to nine lines. It classified into perfect spell and imperfect spell. It has magic function to cure disease; messages delivery function to teach humans about magic, love to help, empathy, respecting teachers, obeying God and the prophets, social relationship, humble; social identity function as the construction built by the community of spell users. Keyword: Treatment Spell, Structure, Function, Language Teaching